Evictions: The Comparative Analysis Problem. Issue 3 (3rd September 2021) - Nelson, Kyle; Garboden, Philip; McCabe, Brian J.; Rosen, Eva
ABSTRACT: Since 2003, when Hartman and Robinson identified eviction as "the hidden housing problem, " a growing body of research has provided detailed, empirical analyses of the eviction process in specific locations. However, there has been little effort to systematically compare the legal regimes and institutional contexts governing eviction proceedings. Drawing on our research in four cities—Baltimore, Maryland; Dallas, Texas; Los Angeles, California; and Washington, DC—we consider how the legal regimes of landlord–tenant courts shape the eviction process for tenants and landlords. Specifically, we draw on fieldwork and administrative records from these four cities to identify how procedural and legal contexts differ by place, and the ways that these processes shape both eviction's institutional life and its underlying social meanings. Although the problem of eviction is no longer hidden in the housing literature, the explosion of eviction research has introduced a comparative analysis problem.